Human papillomavirus (HPV) infection in women of Florianópolis, Santa Catarina, Brazil - Fedrizzi, Edison N.; Schlup, Cristiane G.; Menezes, Maria Elizabeth; Ocampos, Maristela (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: the Human Papillomavirus (HPV) infection is the most frequent sexually transmitted disease in the world and has many clinical mani festations, from asymptomatic infection to invasive carcinoma. At least 50% of sexually active people will have this infection in their life. Objective: to determine the prevalence of HPV and identify the frequency of high risk and low risk virus groups in women attending gynecologic routine as well as evaluate the association between the presence of these viruses and some risk factors. Methods: this is a cross-sectional study. A hundred randomi zed selected women who attended the gynecologic service for routine test were evaluated. All of them had cervical specimens tested for DNA-HPV by the Hybrid Capture II assay and answered a questionnaire to acess risk factors. Results: twenty-one (21%) out of 100 analyzed women showed positivity for DNA-HPV. High risk HPV was detected in 71% and low risk HPV in 52% of positive specimens, including mixed infections. Infection with high risk types was associated with younger age at first sexual intercourse. Other evaluated risk factors such as age, level of education, number of sexual partners, parity, use of oral contraceptives, sexually transmitted disease and smoking did not show relation to HPV infection. Conclusion: the prevalence of HPV in the studied population was 21%, with 71% of high risk virus and 52% of low risk types, including mixed infections. High risk HPV detection was associated with younger age at first sexual intercourse.